PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) TERHADAP LITERASI MATEMATIKA DITINJAU DARI MINAT BELAJAR SISWA - Gayatri Dwi Astuti; Rissa Prima Kurniawati; Naniek Kusumawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematical literacy plays an important role in shaping students' logical thinking skills and solving contextual problems. However, observations at SDN Beji III show that the mathematics learning outcomes of fourth-grade students are still low. Their daily test scores are below the Minimum Competency Criteria (KKM), due to a lack of learning interest and the use of instructional models that do not relate material to real-life contexts. To address this issue, it is necessary to apply a learning model that is relevant to students' daily lives, such as Contextual Teaching and Learning (CTL). This study aims to determine the effect of the CTL learning model on mathematical literacy in terms of students’ learning interest in grade IV at SDN Beji III. This research uses a quantitative approach with a true experimental design, specifically the posttest-only control design. The research subjects consisted of two classes: class IV-A as the experimental class using the CTL model and class IV-B as the control class using the lecture method. Data collection techniques included posttests to measure mathematical literacy and questionnaires to assess students’ learning interest. The data were analyzed using validity tests, reliability tests, normality tests, homogeneity tests, and ANOVA. The results showed that the CTL learning model had a significant effect on students’ mathematical literacy in terms of their learning interest. Students with high learning interest who participated in CTL-based learning showed better outcomes compared to those taught with conventional methods. Therefore, the CTL model can be an effective alternative to improve mathematical literacy among fourth-grade students.